A structural quantitative analysis of services trade de-liberalization - Sven Blank; Peter H. Egger; Valeria Merlo; Georg Wamser (Deutsche Bundesbank, 2018)
This paper suggests a quantifiable multi-sector-multi-country economic model of goods and services production and consumption. It calibrates overall (variable and fixed) costs to market-specific sales by sector and decomposes these costs into observable and unobservable components. In an empirical analysis based on census-type data on firm-sector-country sales of German services sellers as well as sector-country-by-sector-country input-output matrices for various economies and sectors, the paper provides the following insights. The overall (variable and fixed) costs on seller-to-customer-market transactions in services have quite a high distance equivalent and are reduced substantially by preferential market access for services through trade agreements. If all countries considered abandoning existing preferential market access to services, this would reduce their real consumption by up to 7.7 percent with a similar decline in real wages and real dividends (depending on the country). If one country alone abandoned its preferential services market access reciprocally with its partners, the effect would be smaller. However, it would still involve a decline of real consumption of 0.3 percent for a country as large (and as remote relative to continental Europe) as the United Kingdom. For most economies, depending on their input-output structure, de-liberalizing preferential services-market access would have adverse spillover effects on manufacturing (in terms of real wages as well as dividends).
Keywords: F12; F14; F15; F17; L11; L25; 330; Services trade; De-liberalization; Structural estimation; Counterfactual analysis